Tajikistan Economic Report, 2012 : Sustaining Post-Crisis Recovery, Investment and Growth - World Bank (World Bank, 2017)
Tajikistan is one of the world's most remittance-dependent economies, receiving net remittance inflows equivalent to approximately 40 percent of Gross Domestic Product (GDP). Falling remittance inflows was one of the main transmission channels through which the 2008-09 global economic crisis adversely impacted the economy. Conversely, the pickup in growth since 2009 can also be traced to the rebound in remittance inflows (primarily from Russia, where more than 90 percent of Tajik migrants work), which reached 42 percent of GDP in 2010 and an estimated 40 percent of GDP in 2011. As the World Bank's 2011 country economic memorandum has argued, future growth in Tajikistan will depend crucially on increasing efficiency and raising private investment rates. Remittances are likely to grow more slowly than the earlier trend over the last 5-6 years, but could nonetheless be a major contributor to future growth if more go into private investment than in the past.